Dental Caries Among Children Of Age 6- 12 Years Old Visiting A Dental Institution - A Retrospective Study - M, RANGEELA; SANTHANAM, DR. ARCHANA; RAJENDRAN, DR DEEPIKA (The journal of contemporary issues in business and government, 2021)
Introduction: Dental caries is the most common type of oral health problem globally. Despite scientific advance and the fact that caries is preventable, the disease continues to be a major public health problem. In developing countries like India, changing lifestyle and dietary patterns increase the incidence of caries. Dental caries are known to have multifactorial etiology with a number of variables that influence the prevalence of the condition. It refers to the demineralisation of the tooth by the bacteria which occurs when dental plaque adheres to tooth surfaces and becomes colonized by the bacteria. Aim: The aim of this study is to determine the prevalence of dental caries among children less than 12 years. Materials and methods: A total of 4038 patients were retrospectively reviewed from June 2019- March 2020 and included in the study. Demographic details like age, gender and dental status of all the patients were recorded. All the data were entered in the excel sheet. Data was analysed by SPSS software. Chi square test was used to find association between the study variables, where P<0.05 was considered statistically significant. Results: Among the 4038 study subjects of which 2274 were boys and 1764 girls. The prevalence of dental caries is more among 10 years old children (68%) with boy predilection (69%). Mean DMFT score of the population was 4.22. The prevalence of dental caries and age groups were statistically significant ( p < 0.05). Conclusion: This study emphasises the need for treating dental caries at its earliest stage and parents should be aware of caries preventive measures for their children.